2010
DOI: 10.1021/pr100008e
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein A-I Level Is Downregulated in the Granulosa Cells of Patients with Polycystic Ovary Syndrome and Affects Steroidogenesis

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder found in women. The etiology of PCOS is still not clear, and there are no available studies on the proteome analysis of granulosa cells (GCs) in PCOS patients. To identify the pathogenic mechanisms and potential diagnostic markers for PCOS, we conducted proteomic profiling of GCs in PCOS patients by two-dimensional gel electrophoresis and liquid chromatography coupled with mass spectrometry (LC-MS/MS) analyses. The proteomic analysis yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
1
24
0
3
Order By: Relevance
“…Previous proteomic biomarker studies in women with PCOS including one from our group have identified several promising new biomarkers from a variety of tissues in women with PCOS [13][14][15][16][17][22][23][24][25][26][27]. However, we could not identify any study in which any of the biomarkers identified had been validated in independent cohorts of women with PCOS.…”
Section: Introductionmentioning
confidence: 87%
“…Previous proteomic biomarker studies in women with PCOS including one from our group have identified several promising new biomarkers from a variety of tissues in women with PCOS [13][14][15][16][17][22][23][24][25][26][27]. However, we could not identify any study in which any of the biomarkers identified had been validated in independent cohorts of women with PCOS.…”
Section: Introductionmentioning
confidence: 87%
“…The integration of the huge amount of novel information obtained from proteomics may contribute to the elucidation of cellular modifications, resulting in PCOS. A large number of biomolecules involved in metabolism, androgen biosynthesis, or chronic inflammation pathways have been studied in previous reports [1619]. These proteins provide vital information about altered molecular functions in PCOS and raise questions concerning their precise role in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This is the transporter protein of HDL and its down-regulation in both T2DM and PCOS is associated with the reduction of HDL levels (in combination with the proposed increase in fractional HDL clearance especially in T2DM) (42). The reduced levels of ApoA-I present in the granulosa cells of women with PCOS could affect cholesteryl ester uptake, which, in turn, would be expected to disturb normal steroidogenesis pathways by limiting the initial substrate (18). Both these mechanisms could contribute to the increase in prevalence of cardiovascular and cerebrovascular accidents observed in patients with T2DM and PCOS compared with the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…All relevant studies published since the previous database was published were reviewed. Thirteen papers (16,18,19,20,21,22,23,24,25,26,27,28,29) were identified including four review articles and one study on mice. The review articles and the study on mice (21,26,27,29) were excluded apart from a previous review article from our group in which original data on new biomarkers for PCOS had been published (16).…”
Section: Updating the Pcos Proteomics Databasementioning
confidence: 99%
See 1 more Smart Citation